Preparation method and application of environment-friendly stabilizing agent with high selectivity to Cu

By connecting clonamate on the chitosamine to form an amino acid modified shell polynose material, a high -selective CU adsorption stabilizer is prepared to solve the problem of difficulty controlling the risk of copper filtration in sludge gardens. The effective control of CU and the precise governance of soil heavy metal pollution.

CN119371572AActive Publication Date: 2025-01-28ZHEJIANG UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411491505.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

During the use of sludge gardens, how to effectively control the biological effectiveness of copper (Cu), prevent its excessive damage to plant growth, and avoid the risk of copper leaching in heavy rain or acidic rainfall is difficult to control.

Method used

A selective CU adsorption soil heavy metal stabilizer is adopted by a composite method. The ability to selective adsorption CU.

Benefits of technology

This stabilizer can effectively control the risk of Cu's gonorrhea, reduce the toxicity of plants, and coordinate the CU in the miles in the miles to ensure that the plant's extraction of other heavy metals is not affected, thereby achieving the precise governance of soil heavy metal pollution and the precise governance and the precise governance of soil heavy metal pollution. Ecological repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371572A_ABST
    Figure CN119371572A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an environment-friendly stabilizing agent with high selectivity to Cu. The preparation method comprises the following steps: activating carboxyl on L-cysteine by using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) under a certain condition, adding chitosan powder, adjusting the pH until light blue purple precipitate appears, and then performing subsequent treatment to obtain the amino acid modified chitosan porous material. The raw materials are easy to obtain, the preparation method is simple, and reaction conditions are mild; the obtained stabilizing agent can efficiently, rapidly and selectively adsorb Cu, can effectively stabilize Cu in soil, reduces toxicity to plants, and effectively controls the leaching risk of heavy metal Cu in sludge compost soil by cooperating with ryegrass to repair Cu in sludge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of heavy metal stabilizers in soil heavy metal pollution treatment, and in particular to a preparation method of an environmentally friendly high-selectivity Cu stabilizer and application thereof in phytoremediation of heavy metals. Background Art

[0003] Aerobic composting sludge is rich in nitrogen, phosphorus and organic matter. It can be used as a high-quality fertilizer to promote plant growth and improve soil structure through microbial decomposition. The use of compost sludge in garden land can not only avoid the risk of heavy metals entering the human body through the food chain, but also use plants to extract heavy metals in the soil, reducing their content and potential risks in the soil. However, the content of heavy metals in compost sludge is relatively high. Although these heavy metals may be passivated during the fermentation process, reducing their mobility and bioavailability, the total amount of heavy metals has not decreased. At the same time, due to the limited extraction rate of plants, its speed may lag behind the activation rate of soil microorganisms and plant root secretions. Then in the rainy season, these reactivated heavy metals may be washed into the surrounding water bodies by rainwater, threatening the safety of the ecosystem.

[0004] According to the survey, the heavy metal content in the sludge of sewage treatment plants in 40 different regions of my country is Zn>Cu>Cr>Pb>Ni>As>Cd from high to low, among which Cu ranks second. In the sludge in southern my country, the highest concentration of Cu can reach 2867mg / kg. At present, the "Comprehensive Sewage Discharge Standard" (GB8978-1996) followed by my country clearly stipulates that copper is a second-class pollutant, and its primary emission limit is set at 0.5mg / L. The "Surface Water Environmental Quality Standard" (GB3838-2002) stipulates that the standard limit of copper is 1.0mg / L. Given that the environmental capacity has a low tolerance threshold for copper (Cu) and its impact on the soil ecological environment is more sensitive, we must attach great importance to the cumulative effect of copper in composting sludge and its potential environmental risks in the process of promoting the resource utilization of sludge, especially the landscaping application of sludge composting. This requires us to carefully evaluate the concentration level and migration activity of Cu in composting sludge to ensure that its mobility in the soil environment is effectively controlled, thereby reducing its potential risk of harm to the ecological environment outside the soil. On the other hand, although the overall concentration and content of heavy metals in sludge may be high, ecotoxicological studies have shown that the ecological risk of heavy metals is closely related to their chemical forms in sludge. The different forms of heavy metals determine their mobility, bioavailability and potential ecotoxicity in the soil environment. Therefore, the research focuses on the specific existence form of heavy metals, rather than just the total amount. There are different detection methods for the existence form of heavy metals in soil internationally. The most commonly used method is the BCR continuous extraction method. The heavy metal forms are weak acid extraction state (BCR1), reducible state (BCR2), oxidizable state (BCR3) and residual state (BCR4) from low to high stability. After sludge composting, the stability of Cu is improved, and the potential mobility and bioavailability of Cu are reduced. Organic matter accounts for 76.50% of the total Cu content. These organically bound Cu may be converted into more active forms under specific environmental conditions or microbial action, thereby increasing its mobility and bioavailability in the soil. Therefore, when evaluating the environmental behavior of copper in soil and its impact on the ecosystem, the dynamic changes of these organically bound copper and the risk of their potential release must be taken into account. "In particular, heavy metal Cu exhibits higher leaching characteristics under acidic conditions.

[0005] Heavy metal stabilization is the most effective way to control heavy metal leaching. Conventional stabilizers include bentonite, lime and biochar. Heavy metal stabilization is the most effective way to control heavy metal leaching. Conventional stabilizers include natural zeolite, bentonite and biochar. Yang Lan et al. studied the effect of natural zeolite on Pb 2 +, Cu2+, Mn2+, Zn2+ and other heavy metal ions. It was found that natural zeolite has an adsorption effect on Pb 2+ has the strongest adsorption capacity, with a maximum adsorption capacity of 105.26 mg / g, while the adsorption capacity for Cu2+, Mn2+, and Zn2+ decreases in turn, with maximum adsorption capacities of 14.22 mg / g, 12.36 mg / g, and 7.30 mg / g, respectively. 2+ 、Zn 2+ The results showed that under suitable reaction conditions, bentonite has a strong adsorption capacity for Cu 2+ and Zn 2+ The maximum adsorption capacity can reach 60mg / g and 55mg / g. Zhou Wendi found that the hemp stem core biochar can effectively remove Cu in water after modification. 2+ and Ni 2+ , and its maximum adsorption capacity can reach 25.25mg / g and 57.57mg / g. 2+ The maximum adsorption capacity is less than 60 mg / g, and there is a 2+ The defects of weak selectivity and even preferential adsorption of other metal ions. Since these conventional stabilizers do not have selectivity for Cu, the adsorption sites will be occupied by other heavy metals during the application process. To obtain the adsorption effect of the target heavy metal Cu, it is necessary to add a sufficient amount of stabilizer, which not only increases the cost, but also affects the soil structure and physical and chemical properties, and also inhibits the plant's extraction of nutrients and other heavy metals, greatly reducing the ecological and environmental benefits. In view of this, the present invention aims to provide a stabilizer with high selective adsorption of Cu2+, which can be used in combination with plant remediation technology. Through the implementation of the present invention, the leaching risk of Cu can be effectively controlled, while ensuring that the plant's extraction of other heavy metals in the soil is not affected, thereby achieving accurate control and ecological restoration of soil heavy metal pollution. The research and development of the stabilizer of the present invention has important practical significance and urgency for promoting the development of environmentally friendly soil remediation technology and meeting current environmental protection needs.

[0006] Chitosan, a natural polysaccharide, is obtained by deacetylation of chitin, which involves boiling chitin in potassium hydroxide. Chitosan is mainly derived from the shells of insects and marine crustaceans and is the second most abundant biopolymer in nature. Chitosan is not only biodegradable and low-cost, but also has a large number of active functional groups on its molecular backbone, including amino (-NH2) and hydroxyl (-OH), which provide it with abundant active adsorption sites, thus making it exhibit excellent adsorption capacity for heavy metals. Chitosan can be treated with modification techniques such as cross-linking, grafting, composite with other adsorbent materials, and ion templates to further improve its adsorption performance and selectivity for Cu. Summary of the invention

[0007] The present invention aims to solve the problem of controlling the bioavailability of copper (Cu) to prevent it from being too high and causing harm to plant growth during the utilization of sludge in gardening, and avoiding the problem of difficult-to-control copper leaching risk when encountering heavy rainfall or acidic rainfall. To this end, the present invention provides a selective Cu adsorption soil heavy metal stabilizer with a simple synthesis method and low cost and its application. In addition, the present invention also studies the role of the stabilizer in the combined plant remediation process. At the same time, the bioavailability and leaching risk of soil heavy metals in the actual application of the stabilizer are evaluated, providing data support and technical guidance for the resource utilization of sludge. The purpose of the present invention is achieved based on the following technical solutions:

[0008] The first aspect of the present invention provides a method for preparing a stabilizer with high selectivity for Cu.

[0009] Preferably, the preparation method specifically comprises the following steps:

[0010] S1: Weigh 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS) and L-cysteine ​​in sequence and add them to a round-bottom flask, then add a certain volume of water and stir with a constant temperature magnetic stirrer to activate the reactivity of the carboxyl group on L-cysteine, making it easier to react with molecules containing amine groups to form stable amide bonds;

[0011] S2: adding chitosan powder to the mixed solution in step S1, and then adding aqueous hydrochloric acid to dissolve the chitosan, and continuing to stir the reaction for 8 to 12 hours (more preferably 10 hours);

[0012] S3: Slowly add NaOH aqueous solution to the mixed solution in step S2 at a rate of about 2 to 3 drops per second, and measure the pH value in real time with a precise pH test paper, adjust the pH of the mixed solution to 7 to 8, and a light blue-purple precipitate appears, and continue stirring for 2 to 4 hours (more preferably 3 hours) to allow the precipitate to be evenly distributed;

[0013] S4: taking out the mixed solution of step S3, collecting the solid by centrifugation, and obtaining the amino acid-modified chitosan porous material by post-treatment of the obtained precipitate.

[0014] Preferably, in step S1, the masses of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS) and L-cysteine ​​weighed are respectively 0.51-0.65 parts for M1, 0.25-0.35 parts for M2 and 0.9-1.1 parts for M3; in step S1, the mass of water added is 40-60 times the mass of the added powder (M1+M2+M3).

[0015] Preferably, in step S1, the constant temperature stirring conditions are: temperature 20-30°C, time 0.5-2h, more preferably, temperature 25°C, constant temperature stirring time 1h.

[0016] Preferably, in step S2, the mass of chitosan powder added is 0.8-1.2 g, that is, the mass ratio of chitosan powder added to 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is 0.8-1.2:0.51-0.65.

[0017] Preferably, in step S2, the concentration of the hydrochloric acid aqueous solution added is 0.10-0.15 mol / L and the volume is 6-10 ml, that is, the ratio of the hydrochloric acid aqueous solution to the chitosan powder is 6-10 mL: 0.8-1.2 g.

[0018] Preferably, in step S2, the stirring reaction is continued at 20°C to 30°C for 8 to 12 hours, and more preferably, the stirring reaction temperature is 25°C.

[0019] Preferably, in step S3, the concentration of the NaOH aqueous solution is 0.3-1.2 mol / L.

[0020] Preferably, in step S4, the post-treatment includes: washing twice with anhydrous ethanol, washing twice with deionized water (until neutral), and then freezing in an ultra-low temperature refrigerator for 0.5 to 2 hours (more preferably 1 hour), and after the precipitate is completely frozen, placing it in a freeze dryer and freeze-drying it for 68 to 76 hours (more preferably 72 hours).

[0021] The second aspect of the present invention provides an environmentally friendly high-selectivity Cu stabilizer prepared according to the above preparation method.

[0022] The third aspect of the present invention provides an environmentally friendly high-selectivity Cu chitosan-based stabilizer for selectively adsorbing Cu and controlling the risk of heavy metal Cu leaching in sludge, while not affecting plant enrichment and extraction of other heavy metals except Cu.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention synthesized Cys-CS by grafting cysteine ​​onto chitosan, and used chitosan-modified heavy metal adsorbent as soil heavy metal stabilizer. The selective adsorption of Cys-CS in five mixed heavy metal solutions was compared, and the main groups in the material that adsorbed heavy metals with selective adsorption were analyzed by infrared spectroscopy, so as to infer the selective adsorption relationship between the groups and heavy metals. In addition, the adsorption effect and mechanism of the material were inferred by comparing the different adsorption behaviors and adsorption kinetics of the material in single metal solutions and mixed metal solutions. In this work, through adsorption kinetics and isothermal adsorption studies, the adsorption capacity of Cys-CS was 97.8 mg / g. In the presence of Zn 2+ , Pb 2+ 、Cd 2+ 、Ni 2+ In a multi-component system with interfering ions such as 2+ It exhibits excellent selective adsorption performance. The distribution coefficient (k d ) is used as an indicator to measure the interception efficiency of heavy metal ions by the adsorbent. d The values ​​were intuitively compared and analyzed to evaluate and compare the adsorption performance of different adsorbents for target heavy metal ions. The distribution coefficients of Cys-CS for Cu are 11.09 to 118 times that of Pb, 12.17 to 84 times that of Zn, 8.64 to 32.97 times that of Cd, and 32.64 to 46.40 times that of Ni, respectively. This indicates that the stabilizer of the present invention can be tightly bound to Cu(II) in terms of spatial structure and binding site, has good spatial matching, and exhibits specific selective recognition performance. Compared with existing metal stabilizers, the chitosan-based selective stabilizer prepared by the present invention can efficiently, quickly and selectively adsorb Cu, and can effectively stabilize Cu in the soil, reduce toxicity to plants, and cooperate with ryegrass to repair Cu in sludge, effectively controlling the leaching risk of heavy metal Cu in sludge compost soil.

[0025] 2. The method for preparing the environmentally friendly chitosan-based stabilizer with high selectivity of the present invention has simple steps, mild and non-critical reaction conditions, safe process, and does not require a specific reaction device. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The following are SEM and EDS images of the stabilizer of the present invention.

[0027] Figure 2 It is the chemical reaction formula of the stabilizer of the present invention.

[0028] Figure 3 It is the XRD pattern of the stabilizer of the present invention.

[0029] Figure 4It is the FTIR spectrum of the stabilizer of the present invention.

[0030] Figure 5 The figure shows the adsorption of five heavy metals by the stabilizer of the present invention at different pH values.

[0031] Figure 6 It is the adsorption behavior of the stabilizer of the present invention in the mixed system.

[0032] Figure 7 The Langmuir and Freundlich adsorption isotherm model fitting curves of the stabilizer of the present invention.

[0033] Figure 8 The stabilizer of the present invention is Cu 2+ The adsorption kinetics curve.

[0034] Fig. 9 The Cu content in ryegrass was observed 60 days after application of the stabilizer of the present invention.

[0035] Fig.10 The figure shows the change of Cu form in soil 60 days after applying the stabilizer of the present invention.

[0036] Fig.11 The figure is the concentration of heavy metals in the leaching liquid after applying the stabilizer of the present invention.

[0037] Fig.12 It is the concentration factor (BCF) of ryegrass 60 days after applying the stabilizer of the present invention.

[0038] Fig.13 It is the transport coefficient (TF) of ryegrass 60 days after applying the stabilizer of the present invention. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] 0.534 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), 0.320 g of N-hydroxysuccinimide (NHS) and 1.018 g of L-cysteine ​​were weighed and added to a round-bottom flask, and then 100 ml of water was added. The mixture was stirred magnetically at 25° C. for 1 hour to activate the carboxyl group on L-cysteine.

[0042] 1 g of chitosan powder was added to the mixed solution obtained above, and then 10 ml of 0.1 mol / L hydrochloric acid aqueous solution was added to dissolve the chitosan, and stirring was continued at 25° C. for 10 hours.

[0043] The pH of the mixed solution was adjusted to 7-8 by adding 1 mol / L NaOH aqueous solution, and a light blue-purple precipitate appeared. Stirring was continued at 25°C for 3 h to allow the precipitate to be evenly distributed.

[0044] The mixed solution was taken out, collected by centrifugation, washed twice with anhydrous ethanol and twice with deionized water (until neutral), and then placed in an ultra-low temperature refrigerator and frozen at -80°C for 1 hour. After the precipitate was completely frozen, it was placed in a freeze dryer and freeze-dried at -40°C for 72 hours to obtain an amino acid-modified chitosan porous material, which was the final product Cys-CS.

[0045] Example 2

[0046] Weigh 0.1599g, 0.4550g, 0.3802g, 0.4955g and 0.2744g of lead nitrate, zinc nitrate hexahydrate, copper nitrate trihydrate, nickel nitrate hexahydrate and cadmium nitrate tetrahydrate, respectively, add ultrapure water, completely dissolve in an ultrasonic processor, transfer to a 1000ml volumetric flask, rinse three times with ultrapure water in a wash bottle, and finally make up to volume to prepare five 100mg / L single metal solutions.

[0047] The pH was adjusted with 0.1 mol / L nitric acid aqueous solution and 0.1 mol / L sodium hydroxide aqueous solution. A total of five pH values ​​were set, namely 3.5, 4.5, 5.5, 6.0, and 6.5. Three sets of parallel samples were set for each pH value. 25 ml of heavy metal solution was taken into a conical flask, and then 15 mg of material was added and immediately moved to a constant temperature shaker (25 ° C, 150 rpm) for 2 hours. The supernatant was filtered with a 0.45 μm filter membrane and diluted to determine the Cu 2+ 、Zn 2+ , Pb 2+ 、Cd 2+ 、Ni 2+ concentration, and calculate the Cu at different pH values. 2+ 、Zn 2+ , Pb 2+ 、Cd 2+ 、Ni 2+ Adsorption amount. The adsorption amount of five metals by the stabilizer is plotted. Figure 5 .

[0048] Example 3

[0049] Weigh 0.1599g, 0.4550g, 0.3802g, 0.4955g and 0.2744g of lead nitrate, zinc nitrate hexahydrate, copper nitrate trihydrate, nickel nitrate hexahydrate and cadmium nitrate tetrahydrate, put them into a 500ml conical flask, add ultrapure water, place them in an ultrasonic processor until they are completely dissolved, transfer them to a 1000ml volumetric flask, rinse them three times with ultrapure water in a wash bottle, and finally make up the volume to prepare a 100mg / L mixed metal solution. Similarly, prepare 50mg / L, 150mg / L and 200mg / L mixed heavy metal solutions.

[0050] The pH of all mixed solutions was adjusted to 6.0. Three parallel samples were set for each concentration. 25 ml of heavy metal solution was placed in a conical flask, and then 15 mg of material was added. The mixture was immediately moved to a constant temperature shaker (25°C, 150 rpm) and shaken for 2 h. The supernatant was filtered with a 0.45 μm filter membrane and diluted to determine the Cu 2+ 、Zn 2+ , Pb 2+ 、Cd 2+ 、Ni 2+ concentration, and calculate the Cu 2+ 、Zn 2+ , Pb 2+ 、Cd 2+ 、Ni 2+ Adsorption amount. The adsorption amount of five metals by the stabilizer is plotted. Figure 6 .

[0051] In order to more intuitively describe the high selectivity of Cys-CS for Cu, the distribution coefficient K d The adsorption effect of heavy metals by the stabilizer in the mixed system was analyzed. The results are shown in Table 1.

[0052] Table 1 Distribution coefficient of Cys-CS (L / g)

[0053]

[0054] From the experimental results, the stabilizer in the present invention has the highest distribution coefficient for Cu in the concentration range of 50-200 mg / L of mixed heavy metals, and is much higher than the distribution coefficients of other heavy metals, which are 11.09-118 times that of Pb, 8.64-32.97 times that of Cd, 12.17-84 times that of Zn, and 32.64-46.40 times that of Ni.

[0055] Example 4

[0056] Weigh corresponding masses of copper nitrate trihydrate into a beaker, prepare copper nitrate aqueous solutions of 50, 100, 150, 200, 250, 300, 350, and 400 mg / L according to the steps of Example 3, and adjust the pH to 6.0.

[0057] Three parallel samples were set for each concentration gradient. 25 mL of solution was transferred to a conical flask, 15 mg of material was added, and the mixture was placed in a constant temperature shaker (25°C, 200 rpm) for 2 h. The supernatant was filtered with a 0.45 μm filter membrane and diluted to determine the Cu 2+ concentration, and calculate the Cu 2+ The adsorption results were fitted with Langmuir and Freundlich models, and the fitting results are shown in Figure 7 shown.

[0058] Example 5

[0059] Weigh the corresponding mass of copper nitrate trihydrate into a beaker, prepare a 100 mg / L copper nitrate aqueous solution according to the steps of Example 3, and adjust the pH to 6.0. Pipette 25 mL of the metal solution into a conical flask, add 15 mg of the material, set the adsorption time to 1, 2, 5, 10, 20, 50, 70, 90, 120, 150 min, respectively, set three parallel samples for each time, and shake them in a constant temperature shaker (25°C, 200 rpm) in turn. Filter the supernatant with a 0.45 μm filter membrane, dilute and measure the Cu 2+ concentration, and calculate the Cu under different contact time. 2+ Adsorption amount. The pseudo-first-order, pseudo-second-order and Weber-Morris intramolecular diffusion model kinetic models were used for fitting. The fitting results are shown in Figure 8 shown.

[0060] Example 6

[0061] In order to explore the application effect of the stabilizer of the present invention in soil, we set up a pot experiment and a leaching experiment. The pot experiment evaluated the stabilizing effect of the stabilizer on copper in the soil environment by studying the changes in copper content in plants and copper forms in soil.

[0062] The pot experiment was conducted under outdoor natural conditions, and ryegrass was planted in polyethylene pots with a diameter of 15.5 cm and a height of 16.7 cm. A total of 3 groups were set up for the pot experiment, and three parallel samples were set up in each group, as shown in Table 2. 1 kg of soil was added to each pot, of which no material was added to the control group CK, and 0.5‰ (weight ratio) of Cys-CS and 2‰ of Cys-CS were added to the other two groups, respectively, and the soil was fully mixed. A layer of absorbent paper was spread on the culture dish, an appropriate amount of tap water was added, and then the ryegrass seeds were spread on the paper. After about 7 days, the seeds germinated into seedlings. In each pot, 25 seedlings with similar growth conditions were transplanted. Water appropriately according to the actual soil moisture content. A total of 60 days were spent from transplantation to harvesting.

[0063] Table 2 Pot test

[0064]

[0065] To collect plant samples, the soil and other debris on the surface of the plant roots must be removed first. The ryegrass must be washed several times with tap water and ultrapure water. The ryegrass must then be placed in a forced air drying oven and dried at 105°C for 30 minutes. The dried roots and stems must then be ground to 100 mesh and stored for testing.

[0066] After digestion and acid removal of plant samples, the Cu content in the samples was determined. The results of the changes in Cu content in plants are as follows: Fig. 9 shown.

[0067] To collect soil samples, the soil needs to be naturally air-dried in a well-ventilated place indoors, and then the appropriate amount of soil is ground using the quartering method. First, the sample is coarsely ground, spread on kraft paper, and pressed with a wooden stick to pick out impurities such as plant residues and stones. A balloon is rubbed against the cloth to absorb the tiny and broken plant roots through static electricity. The crushed soil sample is ground to 100 mesh and sieved for soil heavy metal analysis.

[0068] The determination of soil heavy metal forms adopts the improved BCR continuous extraction method, which divides heavy metal forms into four types according to stability, from low to high: weak acid extraction state, reducible state, oxidizable state, and residual state. Fig.10 The changes in the morphological distribution of Cu in soil under different Cys-CS addition amounts are shown.

[0069] Example 7

[0070] Leaching is one of the most important ways that heavy metals in soil may cause environmental pollution, and the leaching experiment can simulate the release of heavy metal elements in the soil to the surrounding environment when the soil is exposed to leaching by precipitation to the greatest extent. By comparing the leaching test results with and without the application of the stabilizer of the present invention, the ability of the stabilizer to control the leaching risk of heavy metals can be effectively evaluated.

[0071] The leaching experiment used a 15cm diameter, 65cm high transparent PVC tube as the leaching column. The leaching column was filled with 5cm gravel, 40cm normal soil and 15cm compost soil from bottom to top. The control group CK did not add any materials, and the other group added 0.5‰ Cys-CS to the compost soil. Simulating the natural rainwater in Hangzhou, 0.25mg / L H2SO4 and 0.05mg / L HNO3 solution were used as SO4 2- :NO3 - =5:1 ratio to prepare the stock solution, and dilute it with ultrapure water to simulate rainwater with pH=5.0. The leaching water volume is adjusted by a peristaltic pump, and the leaching water volume simulates the highest precipitation of 135.3 mm in Jiashan, Zhejiang during the "Tali" typhoon. The calculation formula for the precipitation volume of the leaching column is as follows. The average radius of the flower pot is 7.5 cm. Through calculation, the simulated leaching rainwater volume in this experiment is 1.67L. A layer of 120 mesh filter is fixed under the leaching column to prevent impurities from entering the PVC box. After the experiment, the PVC box cover is sealed and the leaching liquid is tested.

[0072] V=α×A×h×10 -4

[0073] Where: V——rainfall volume, L;

[0074] α——runoff loss coefficient, taken as 0.7;

[0075] A——Cross-sectional area of ​​leaching column, cm 2 ;

[0076] h—— rainfall in 1 hour, mm.

[0077] Determine the contents of Cu, Pb, Zn, Cd and Ni in the leaching liquid. Fig.11 The concentration changes of each heavy metal in the leachate under different treatments are shown.

[0078] The chitosan-based stabilizer with high selectivity for Cu of the present invention is composed of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS), and L-cysteine ​​as auxiliary materials (step S1), chitosan powder as the main material (step S2), and then the pH is adjusted with sodium hydroxide aqueous solution and the amino acid-modified chitosan porous material is obtained by subsequent treatment (steps S3 and S4). Therefore: Figure 1 (a) (b) are the morphologies of the final product Cys-CS; Figure 1 (c) is the XRD pattern of the product, in which there is a large peak at a 2θ angle of 11.9°, and a narrow and sharp diffraction peak at 20.6°, indicating that Cys-CS has a certain degree of crystallinity.

[0079] like Figure 1 As shown, Figure a is a cross-sectional view of the material, which shows that the interior of Cys-CS is in the form of curled sheets that are interlaced with each other. When the layered structure is observed by zooming in to 1 μm, it can be found that the surface of the material is covered with many holes, which is conducive to the diffusion of heavy metal ions into the interior of the hydrogel. In addition, these pores have a large specific surface area and a large number of active sites, which are conducive to the adsorption of heavy metal ions. In terms of elemental composition, it can be seen from Figure c that the weight percentages of C, N, O, and S in Cys-CS are 51.32%, 10.41%, 35.45%, and 2.82%, respectively, as shown in Table 3. The detection of the S element indicates that cysteine ​​is grafted onto chitosan. According to the atomic number ratio of the elements C:N:S:O in Table 3, which is 4.28:0.74:0.09:2.22, its molecular formula is inferred to be C 97 H 205 N 15 O 56 S2. Based on the chemical reaction formula, the chemical structure of the product is inferred to be as follows Figure 2 shown.

[0080] Table 3 Elemental analysis of Cys-CS

[0081]

[0082] like Figure 3 As shown in the figure, Cys-CS has a large peak at a 2θ angle of 11.9°, and a narrow and sharp diffraction peak at 20.6°, indicating that Cys-CS has a certain degree of crystallinity.

[0083] like Figure 4 As shown, after reacting with cysteine, a 1652 cm -1 The peak at 1656 cm -1 , and there is an enhancement, which is because the reaction produces an amide bond, which corresponds to C=O. -1 A new peak is generated at 2866 cm, which is caused by the stretching vibration of the sulfur-oxygen double bond in S=O, which means that part of -SH is oxidized to S=O. -1 The nearby band was identified as -NH, which shifted to 2890 cm after Cu adsorption. -1 , and the absorption peak intensity also weakens. At 1366cm -1 The nearby band was identified as -NH2, which shifted to 1323 cm after Cu adsorption. -1 The absorption peak intensity also becomes stronger. -1 and 1587cm -1The nearby bands were identified as C=O and -NH. After Cu adsorption, the peak of the C=O group disappeared, and the double peak merged into a single peak, shifting to 1615 cm -1 This indicates that there is a strong interaction between -NH2 and amide groups and metal ion Cu.

[0084] like Figure 5 As shown in the figure, Cys-CS obviously has a better adsorption effect on Cu, and the adsorption amount of the other four heavy metals is very low. It can be seen that when pH = 3.5-6, the adsorption amount of Cu by Cys-CS shows a slow growth trend with the increase of pH, and at pH = 6, the adsorption amount reaches 46.6 mg / g. At pH = 6.5, its adsorption amount of Cu reaches 72.7 mg / g, which is much higher than the adsorption amount at any other pH value. This is because it was found during the experiment that some Cu ions in the solution at this pH value precipitated, resulting in pseudo-adsorption, so the adsorption amount at this pH value was ignored.

[0085] like Figure 6 As shown in Figure a, it can be seen that in the mixed solution, the adsorption amount of Cu by Cys-CS is much higher than that of other heavy metals, which corresponds to the result that Cys-CS has the highest adsorption amount of Cu in the single metal solution in the pH experiment. As can be seen from Figure b, the order of the adsorption amount of Cys-CS to the five heavy metals is as follows: Cu (0.687-1.718 mmol / g)>Cd (0.016-0.120 mmol / g)>Zn (0.020-0.095 mmol / g)>Pb (0.003-0.058 mmol / g)>Ni (0.026-0.053 mmol / g). By comparison with the pH experiment, when the pH is equal to 6, in the 100 mg / L mixed system, the adsorption amount of Cu by Cys-CS is 77.5 mg / g, which is higher than the adsorption amount in the 100 mg / L single metal Cu solution.

[0086] like Figure 7 As shown, this study uses the Langmuir and Freundlich adsorption isotherm models to explain the mechanism of heavy metal adsorption by the material. The Langmuir adsorption isotherm model assumes that the adsorbent surface is uniform and the adsorbate forms a uniform monolayer adsorption on its surface. The Freundlich model assumes that the adsorption process is not uniform, but multilayer adsorption. The Langmuir model is more suitable for describing the adsorption process of heavy metals by the material of the present invention. According to the model, it is calculated that the maximum adsorption amount of Cys-CS for Cu is 97.8 mg / g, which is close to the maximum adsorption amount actually measured.

[0087] like Figure 8As shown in a, the adsorption of Cu by Cys-CS is a slow process, and the adsorption equilibrium is reached at about 150 min, and the maximum adsorption amount is 43.6 mg / g. The fitting coefficient R of the pseudo-second-order reaction kinetic model of Cys-CS 2 is 0.9394, which is higher than pseudo-first order, indicating that chemical adsorption is the main adsorption mode. Figure 8 As shown in Figure 2, the adsorption process of the material is divided into three stages. The first stage is the instantaneous adsorption stage, in which the metal ions can quickly diffuse to the surface of the material and be captured by the groups, presenting a rapid adsorption process. The K 1id The second stage is the internal diffusion adsorption stage, in which the heavy metal ions begin to diffuse into the interior of the material, and the adsorption rate slows down. 2id The third stage is the adsorption equilibrium stage. In this stage, the adsorption of heavy metals by the groups on the surface of the material reaches saturation and is in equilibrium. The K of Cys-CS 3id is 0.35. The K of the stabilizer 1id Much larger than K 2id , reaching 2.3 times, which shows that intraparticle diffusion is the rate-limiting stage for the adsorption of heavy metals by the stabilizer. Secondly, it can be found that the fitting curve of the intraparticle diffusion model of Cys-CS does not pass through the origin, indicating that the adsorption process is controlled by both intraparticle diffusion and surface diffusion. By comparing the proportion of adsorption in each stage, it can be found that the adsorption of Cu by Cys-CS mainly occurs in the intraparticle diffusion stage.

[0088] like Fig. 9 As shown in the figure, the addition of stabilizer reduced the Cu content of the aboveground and underground parts of ryegrass. At a dosage of 0.5‰, the Cu content of the aboveground and underground parts decreased by 11.64% and 1.86%, respectively; at a dosage of 2‰, the Cu content of the aboveground and underground parts decreased by 16.8% and 15.9%, respectively. This also shows that the stabilization effect of Cys-CS on Cu is stronger when the dosage is high.

[0089] like Fig.10As shown in the figure, the forms of Cu in each treatment group are mainly BCR4 and BCR3. With the addition of stabilizer, the form distribution of Cu in soil has changed significantly, among which BCR1 and BCR2 show a decreasing trend and the proportion is inversely proportional to the dosage. The higher the dosage, the more obvious the decrease. Among them, BCR1 decreased from 14% in the CK group to 8%-9%, a decrease of 35.7%-42.9%, and BCR2 also decreased to a certain extent, from 6% to 5% and 4%. Correspondingly, BCR3 and BCR4 increased significantly, among which the increase ratio of BCR3 was greater than that of BCR4, BCR3 increased from 37% to 42%-43%, while BCR4 only increased from 42% to 44%-45%. The reason for the above phenomenon is that Cys-CS adsorbs acid-extractable Cu in the soil and converts it into organically bound Cu, thereby increasing the proportion of oxidizable Cu. On the other hand, some oxidizable Cu will also combine with mineral components in the soil and convert into residual state.

[0090] like Fig.11 As shown, after the application of Cys-CS, the contents of Zn, Cd, and Ni in the leaching liquid did not change significantly. The concentration of Cu in the CK group was 0.143 mg / L, reaching the Class III standard for groundwater. The application of the stabilizer significantly reduced the Cu concentration, which dropped to 0.045 mg / L, a decrease of 68.53%, so that the leaching liquid reached the Class II standard. The concentration of Pb in the CK group was 0.189 mg / L, and after the addition of Cys-CS, it dropped to 0.106 mg / L, a decrease of only 43.92%, and the leaching liquid still did not reach the Class IV standard. Therefore, in soil remediation practice, the material of the present invention exhibits significant selective adsorption characteristics, which helps to reduce the leaching risk of target heavy metals and has good application prospects in the field of soil remediation.

[0091] like Fig.12As shown in the figure, the order of ryegrass's ability to accumulate various metals is Cd>Cu>Zn>Ni>Pb. The plant enrichment factor (BCF) indicates the plant's ability to accumulate heavy metals, which refers to the ratio of the heavy metal concentration in the plant roots to the heavy metal concentration in the soil. The higher the BCF value, the stronger the plant's ability to stabilize heavy metals. The plant enrichment factor value of Cd reached as high as 1.57, which is mainly because the Cd content in the sludge compost soil is much lower than the other four heavy metals, and BCF is the concentration of heavy metals in the roots divided by the concentration of heavy metals in the soil, so the BCF value of Cd is much higher than that of other heavy metals. The BCF value of Pb is the lowest, only 0.337, because Pb has a strong stress-inhibiting effect on plants, and the Pb content in the experimental soil is relatively high. After adding the stabilizer, the BCF values ​​of Ni and Cd did not change significantly, indicating that the addition of the stabilizer has almost no effect on the enrichment of Ni and Cd by ryegrass. The addition of Cys-CS reduces the BCF value of Cu by 8.7% to 15.4%, indicating that the stabilizer of the present invention has high selectivity and excellent adsorption capacity for Cu in the soil. After the stabilizer of the present invention is added to the soil, the Cu in the soil is first fixed, which not only reduces the mobility and bioavailability of Cu, but also increases the resistance of the roots to absorb Cu due to the influence of the rhizosphere environment, and increases with the increase of the addition ratio.

[0092] like Fig.13 As shown in the figure, in the CK group, the plant transport coefficient (TF) values ​​of the five heavy metals were in the order of Cd>Zn>Pb>Ni>Cu, and the transport coefficients of ryegrass for Cu, Zn, Pb, Cd, and Ni were 0.061, 0.423, 0.105, 0.738, and 0.189, respectively. After adding the stabilizer, there was no significant effect on the TF values ​​of the five heavy metals, which indicates that the addition of the stabilizer will not affect the plant's ability to transport heavy metals. Therefore, while Cys-CS stabilizes Cu, it will not affect the extraction capacity of ryegrass for the heavy metal.

Claims

1. A method for preparing an environmentally friendly Cu-selective stabilizer, characterized in that: The following steps are involved: S1: Weigh 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and L-cysteine ​​and add them into a reactor, then add water and stir with magnetic force at constant temperature to obtain a mixed solution; S2: adding chitosan to the mixed solution in step S1, then adding aqueous hydrochloric acid to dissolve the chitosan, and continuing to stir the reaction to form a reaction system; S3: Add a NaOH aqueous solution dropwise to the reaction system obtained in step S2, adjust the pH of the solution to 7-8, and a light blue-purple precipitate appears. Continue stirring to allow the precipitate to be evenly distributed to obtain a mixed solution; S4: taking out the mixed solution of step S3, collecting the solid by centrifugation, and obtaining the amino acid-modified chitosan porous material through post-treatment, that is, an environmentally friendly stabilizer with high selectivity for Cu.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and L-cysteine ​​is 0.51-0.65:0.25-0.35:0.9-1.

1.

3. The preparation method according to claim 1, characterized in that: In step S1, the mass of water added is 40-60 times the total mass of the added 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and L-cysteine.

4. The preparation method according to claim 1, characterized in that: In step S1, the conditions for constant temperature magnetic stirring are: temperature 20-30° C., time 0.5-2 h.

5. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the added chitosan powder to the mass ratio of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is 0.8-1.2:0.51-0.

65. In step S2, the concentration of the added hydrochloric acid aqueous solution is 0.10-0.15 mol / L, and the ratio of the hydrochloric acid aqueous solution to the chitosan powder is 6-10 mL: 0.8-1.2 g.

6. The preparation method according to claim 1, characterized in that: In step S2, the reaction is continued to be stirred at 20°C to 30°C for 8 to 12 hours.

7. The preparation method according to claim 1, characterized in that: In step S3, the concentration of the NaOH aqueous solution is 0.3-1.2 mol / L.

8. The preparation method according to claim 1, characterized in that: In step S3, stirring is continued at 20-30° C. for 2-4 h.

9. The preparation method according to claim 1, characterized in that: In step S4, the post-treatment includes: washing with anhydrous ethanol, washing with deionized water, and then freezing in a refrigerator for 0.5 to 2 hours, and after the precipitate is completely frozen, placing it in a freeze dryer and freeze drying it for 68 to 76 hours.

10. Use of the environmentally friendly Cu-selective stabilizer prepared by the preparation method according to any one of claims 1 to 9 in assisting plants in extracting heavy metals.

Citation Information

Patent Citations

  • L-cysteine / chitosan-modified electrochemical sensor and use thereof

    CN101793862A

  • Preparation method of sulfhydrylation magnetic chitosan composite material for removing heavy metal ions

    CN106076274A

  • Composite adsorbent for adsorbing heavy metal lead in sewage

    CN109569530A

  • Chitosan modified heavy metal chelating agent

    CN113289588A

  • High-conductivity heavy metal ion imprinting electrode and preparation and application thereof

    CN115248239A